Are Frozen Sections and MSIS Criteria Reliable at the Time of Reimplantation of Two‐stage Revision Arthroplasty?. Issue 7 (July 2016) - George, Jaiben; Kwiecien, Grzegorz; Klika, Alison K.; Ramanathan, Deepak; Bauer, Thomas W.; Barsoum, Wael K.; Higuera, Carlos A.
Abstract: Background: Frozen section histology is widely used to aid in the diagnosis of periprosthetic joint infection at the second stage of revision arthroplasty, although there are limited data regarding its utility. Moreover, there is no definitive method to assess control of infection at the time of reimplantation. Because failure of a two‐stage revision can have serious consequences, it is important to identify the cases that might fail and defer reimplantation if necessary. Thus, a reliable test providing information about the control of infection and risk of subsequent failure is necessary. Questions/purposes: (1) At second‐stage reimplantation surgery, what is the diagnostic accuracy of frozen sections as compared with the Musculoskeletal Infection Society (MSIS) as the gold standard? (2) What are the diagnostic accuracy parameters for the MSIS criteria and frozen sections in predicting failure of reimplantation? (3) Do positive MSIS criteria or frozen section at the time of reimplantation increase the risk of subsequent failure? Methods: A total of 97 patients undergoing the second stage of revision total hip arthroplasty or total knee arthroplasty in 2013 for a diagnosis of periprosthetic joint infection (PJI) were considered eligible for the study. Of these, 11 had incomplete MSIS criteria and seven lacked 1‐year followup, leaving 79 patients (38 knees and 41 hips) available for analysis. At the time of reimplantation, frozen section results were compared with modified MSIS criteria as the gold standard in detecting infection. Subsequently, success or failure of reimplantation was defined by (1) control of infection, as characterized by a healed wound without fistula, drainage, or pain; (2) no subsequent surgical intervention for infection after reimplantation surgery; and (3) no occurrence of PJI‐related mortality; and diagnostic parameters in predicting treatment failure were calculated for both the modified MSIS criteria and frozen sections. Results: At the time of second‐stage reimplantation surgery, frozen section is useful in ruling in infection, where the specificity is 94% (95% confidence interval [CI], 89%‐99%); however, there is less utility in ruling out infection, because sensitivity is only 50% (CI, 13%‐88%). Both the MSIS criteria and frozen sections have high specificity for ruling in failure of reimplantation (MSIS criteria specificity: 96% [CI, 91%‐100%]; frozen section: 95% [CI, 88%‐100%]), but screening capabilities are limited (MSIS sensitivity: 26% [CI, 9%‐44%]; frozen section: 22% [CI, 9%‐29%]). Positive MSIS criteria at the time of reimplantation were a risk factor for subsequent failure (hazard ratio [HR], 5.22 [1.64‐16.62], p = 0.005), whereas positive frozen section was not (HR, 1.16 [0.15‐8.86], p = 0.883). Conclusions: On the basis of our results, both frozen section and MSIS are recommended at the time of the second stage of revision arthroplasty. Both frozen section and modified MSIS criteria had limited screening capabilities to identify failure, although both demonstrated high specificity. MSIS criteria should be evaluated at the second stage of revision arthroplasty because performing reimplantation in a joint that is positive for infection significantly increases the risk for subsequent failure. Level of Evidence: Level III, diagnostic study.